2017
DOI: 10.4172/2161-1165.1000323
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practice of Physicians towards Clinical Pharmacy Services in Ten Public Hospitals in Oromia Regional State, Ethiopia

Abstract: Objective: The purpose of this study was to assess knowledge, attitudes and practice of medical doctors in some selected public hospitals towards Clinical Pharmacy Services in Ethiopia. Methodology:Cross sectional study design was employed to assess knowledge, attitude and practices of medical doctors towards clinical pharmacy services. The study population was selected using simple random sampling technique. Self-administered questionnaires were used to extract relevant information from the study subjects. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Nonetheless, doctors believe pharmacists should be in the wards to answer drugrelated issues and not otherwise. Generally, these findings are in concordance with previous studies [23,24]. In the eyes of doctors and other healthcare workers, pharmacists' primary role is drug formulation and dispensing and should not involve direct patients care [21,27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nonetheless, doctors believe pharmacists should be in the wards to answer drugrelated issues and not otherwise. Generally, these findings are in concordance with previous studies [23,24]. In the eyes of doctors and other healthcare workers, pharmacists' primary role is drug formulation and dispensing and should not involve direct patients care [21,27].…”
Section: Discussionsupporting
confidence: 91%
“…Doctors are not always aware of what pharmacists can offer and how they can collaborate to maximize patient care. In a study involving thirteen physicians, almost all were not aware of the level of clinical training pharmacists received but saw the need for collaborating [23], mainly in reducing medication-related errors, health-related costs, and the detection and management of adverse drug reactions [24]. Conversely, pharmacists are not always concerned with physicians' expectations when developing clinical pharmacy activities [22].…”
Section: Introductionmentioning
confidence: 99%
“…While most participants reported that clinical pharmacists should leave patient care to other healthcare members and care about drug products, this was expected since many low-income nations reported that the responsibilities of the clinical pharmacist have been defined as subordinate to those of physicians. 13 , 25 One probable explanation for these perceptions is that physicians are unaware of clinical pharmacists’ expertise. When the clinical pharmacist and the physician continue to communicate and the pharmacist can share his or her expertise, physicians may see the clinical pharmacist’s potential and significance to the health care team.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] The third part was concerned with barriers that may hinder clinical pharmacists' contributions to the health care team; those questions were adopted from existing literature. 12,13 Two independent academic members from the faculty of pharmacy pre-tested the questionnaire for suitability and content relevance. The questionnaire was additionally reviewed by the other three physicians for relevance, clarity, conciseness, and simplicity of the items.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation